International Prosecution of Human Rights Crimes - Kaleck, Wolfgang (SpringerLink Bücher, 2007)
The book explores recent developments in the international and national prosecution of persons accused of committing war crimes and crimes against humanity. It considers the relationship between national and international law, science and practice, with emphasis on the emerging principle of universial jurisdiction and the effect of 'the war on terror' on legal norms.